Effect of Snoring and Smoking on Blood Lipid Levels - Yazar, H.; Tiftik, A.M.; Buyukbas, S. (Asian Journal of Chemistry, 2010)
This study reports the relationship with snore (obstructive sleep apnea syndrome, OSAS), cigarette smoking and blood lipid levels in human. This work carried out on adult patients (age: 25-55) who applied to the polyclinic of Cumra Public Hospital between January 2005 and November 2006, of 598 women and 408 men. As a result, it has been found that the snoring and cigarette smoking adversely effect on blood lipid levels.